Prognosis of Nonagenarian ICU Patients A Bayesian analysis of prospective European studies - Daniel Dankl; Raphael Romano Bruno; Michael Beil; Hans Flaatten; Malte Kelm; Sviri Sigal; Wojciech Szczeklik; Muhammed Elhadi; Michael Joannidis; Andreas Koköfer; Barbara Schreiber; Franz Singhartinger; et al. (Annals of Intensive Care, 2025)
Abstract Background As the population ages, the number of very elderly patients (≥ 90 years, nonagenarians) admitted to intensive care units (ICUs) is increasing. This trend raises concerns about the appropriateness of ICU care for this age group, especially due to the uncertainty surrounding their prognosis. Some studies suggest that elderly ICU patients have outcomes similar to slightly younger patients, but skepticism remains due to clinical judgment, cultural attitudes, and resource allocation concerns. Methods We reassessed the 30-day mortality risk of nonagenarians admitted to ICUs using data from the VIP1, VIP2, and COVIP registries. Bayesian statistical methods, including Markov Chain Monte Carlo (MCMC) simulations, were used to estimate the relative risk (RR) of mortality for nonagenarians compared to octogenarians (80–89 years). Various prior assumptions (non-informative, pessimistic, and skeptical) were incorporated. The analysis adjusted for key variables such as SOFA score, frailty, and treatment limitations. Results A total of 8,408 patients were included, consisting of 807 nonagenarians and 7,601 octogenarians. The 30-day mortality rate was 45% for nonagenarians and 42% for octogenarians (p = 0.12). Bayesian analysis revealed a high probability (81.1–97.9%) that nonagenarians face a higher 30-day mortality risk. However, the probability of a clinically significantly increase in mortality (RR > 1.1) was moderate (28.9–34.7%), and the probability of a substantial increase (RR > 1.2) was very low (0.03–1.9%). Conclusion Nonagenarians in the ICU have a slightly higher 30-day mortality risk compared to octogenarians, but the increase is unlikely to exceed clinically meaningful thresholds. Bayesian methods offer more refined mortality risk assessment, suggesting that ICU admission decisions should be based on individualized factors, not just age.